Large contribution of boreal upland forest soils to a catchment‐scale CH4 balance in a wet year. Issue 6 (24th March 2016) - Lohila, Annalea; Aalto, Tuula; Aurela, Mika; Hatakka, Juha; Tuovinen, Juha‐Pekka; Kilkki, Juho; Penttilä, Timo; Vuorenmaa, Jussi; Hänninen, Pekka; Sutinen, Raimo; Viisanen, Yrjö; Laurila, Tuomas
Abstract: Upland forest soils affect the atmospheric methane (CH4 ) balance, not only through the soil sink but also due to episodic high emissions in wet conditions. We measured methane fluxes and found that during a wet fall the forest soil turned from a CH4 sink into a large source for several months, while the CH4 emissions from a nearby wetland did not increase. When upscaled to the whole catchment area the contribution of forests amounted to 60% of the annual CH4 emission from the wetlands, while in a normal year the forest soil consumes 10% of the wetland emission. The period of high upland soil emission was also captured by the nearby atmospheric concentration measurement station. Since the land cover within the catchment is representative of larger regions, our findings imply that upland forests in the boreal zone constitute an important part in the global CH4 cycle not previously accounted for. Key Points: In a wet fall, upland forest turns from a CH4 sink to source, while wetland emissions do not change The monthly catchment‐scale emission from upland forest can be more than twice that from wetlands Upland forests in the boreal zone may constitute an important part in the global CH4 cycle